Preparation and application of MOFs modified wood-based self-supporting conductive framework
By using MOFs in lithium-sulfur batteries to modify the wood-based self-supported conductive framework, the problem of limited electrochemical performance of LSB is solved, and higher energy density and better electrochemical performance are achieved.
Patent Information
- Application Number
- CN202411427470.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-10-14
AI Technical Summary
The electrochemical properties of lithium-sulfur batteries (LSBs) are subject to the low conductivity of the final product of sulfur and sulfur discharge, the positive electrode volume changes and the polysulfide shuttle effect, resulting in poor performance under high energy and high power density requirements.
The wood-based self-supported conductive framework is modified by MOFs. By loading MOFs nanoparticles into the wood-based carbon film, a convenient ion and electron channel is formed, and sulfur loading and reaction sites are increased, while the sulfur loading is regulated to achieve dynamic balance of electrochemical performance.
It improves the energy density of lithium-sulfur batteries, simplifies the electrode preparation process, reduces production costs, and improves the cycle life and rate performance of the battery.
Smart Images

Figure CN119581471A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium-sulfur battery electrode materials, and in particular to a preparation method and application of a MOFs-modified wood-based self-supporting conductive skeleton. Background Art
[0002] Lithium-ion batteries have dominated the electronics and power battery market for more than 30 years, but they can no longer meet the current demand for high energy and high power density. Lithium-sulfur batteries (LSBs) have the advantages of high theoretical specific capacity (1675mAh / g), low cost, and green environmental protection, and are considered to be one of the most promising energy storage technologies to replace lithium batteries. However, the marketization of LSBs is affected by some of their own defects: the low conductivity of sulfur and the final discharge product of sulfur (Li2S2 / Li2S), the volume change of the positive electrode, and the polysulfide shuttle effect, all of which greatly affect the electrochemical performance of LSBs.
[0003] To solve the development problems of LSB, metal organic framework materials (MOFs) and their derivatives have been used in LSB modification research and have improved the electrochemical performance of LSB to a certain extent. However, MOFs-derived nanoparticles are independent and not connected, which seriously hinders the transfer of electrons between them. In addition, these nanoparticles are prone to accumulation and agglomeration, resulting in a reduction in the exposed specific surface area and active sites, thereby weakening the adsorption of LiPSs.
[0004] In order to make full use of the active sites of MOFs materials, choosing a suitable catalyst carrier can accelerate the transmission of ions and electrons between nanoparticles and effectively alleviate the shuttling effect of polysulfides. The mainstream solution is to combine it with a carbon matrix. The introduction of conductive agents and binders in traditional coated positive electrodes will reduce the actual energy density and sulfur loading of the electrode, while the self-supporting positive electrode is an integrated conductive skeleton with adjustable structure, which can be directly used as a positive electrode carrier. Biomass materials are a renewable resource rich in carbon elements, and the most common ones are animal and plant derivatives and agricultural waste. It has outstanding advantages such as wide sources, low cost, environmental sustainability and rich structure, so it has broad application prospects in LSB self-supporting positive electrode carbon carriers. Selecting suitable biomass self-supporting materials as catalyst carriers for MOFs is a key issue currently faced. Summary of the invention
[0005] In order to overcome the defects of the above prior art, the present invention proposes a preparation method and application of a MOFs-modified wood-based self-supporting conductive skeleton, which can provide convenient ion and electron channels and more sulfur loading and reaction sites. In addition, the self-supporting positive electrode is easy to control the thickness, and can flexibly control the sulfur loading, achieve a dynamic balance between sulfur loading and electrochemical performance, and ultimately achieve the purpose of improving energy density.
[0006] A method for preparing a MOFs-modified wood-based self-supporting conductive skeleton comprises the following steps:
[0007] Step (1): firstly cut a commercially available wood block along a vertical growth direction and punch it with a cutter to obtain a thin disc with uniform thickness and diameter; boil the thin disc in deionized water and then add a buffer solution containing 1% NaClO2 and 5% CH3COONa to perform chemical delignification treatment; then take out the thin disc and repeatedly rinse it with ethanol until it is neutral to obtain delignified wood chips;
[0008] Step (2): dissolving metal salts and surfactants of different masses in deionized water to obtain a metal salt solution, adding the delignified wood chips obtained in step (1) into the metal salt solution and stirring with a magnetic stirrer to obtain a wood chip metal salt solution;
[0009] Step (3): dissolving an organic ligand and a capping agent in deionized water to obtain a ligand solution, slowly adding the ligand solution to the wood chip metal salt solution, vigorously stirring with a magnetic stirrer, and then aging at room temperature. After aging, the MOFs-modified wood chips are taken out and washed with deionized water and ethanol;
[0010] Step (4): the MOFs-modified wood chips are frozen and transferred to a freeze dryer for drying, and then neatly arranged and sandwiched between two graphite plates, placed in a tubular furnace, and subjected to a carbonization process under the protection of a reducing gas atmosphere to obtain a MOFs-modified wood-based carbon film;
[0011] Step (5): The MOFs-modified wood-based carbon film is placed in a glove box, fixed on a rotating table for rotation, and a DOL / DME mixed solution containing Li2S8 is added dropwise. After standing, a MOFs-modified wood-based carbon film-loaded sulfur self-supporting positive electrode is obtained, i.e., a MOFs-modified wood-based self-supporting conductive skeleton.
[0012] Specifically, the commercially available wood block in step (1) is one of balsa wood, poplar wood, plank wood, basswood, and pine wood; the wood chip has a thickness of 1-3 mm and a diameter of 16-20 mm.
[0013] Specifically, the metal types corresponding to the metal salts described in step (2) are one or more combinations of Fe, Co, Ni, Zn, and Cu, the surfactant is one or more combinations of polyvinyl pyrrolidone (PVP) and polyethylene glycol (PEG), the concentration range of the metal salt is 1-6 mmol, the surfactant is 0.01-0.06 g, and the stirring time of the magnetic stirrer is 6-8 h.
[0014] Specifically, the organic ligand described in step (3) is one or a combination of 2-methylimidazole and terephthalic acid, and the concentration range of the organic ligand is 8-144mmol; the magnetic stirring time is 1-3h; the aging time is 6-18h; the capping agent is one or more combinations of hexadecyltrimethylammonium bromide (CTAB) and polyvinyl alcohol (PVA), and the capping agent is 0.01-0.13g.
[0015] Specifically, the MOFs in step (3) are ZIF-67, ZIF-8, MIL-53 and other types of MOFs materials.
[0016] Specifically, the drying temperature in step (4) is -55°C, 100Pa, and the time is 12h.
[0017] Specifically, in step (4), the temperature rise rate of the tube furnace sintering is controlled to be 2-10°C / min, and the high temperature sintering is carried out at 700-900°C for 2-4h.
[0018] Specifically, the MOFs-modified wood chips in step (4) are MOFs-loaded wood matrix, and MOFs crystals are successfully loaded inside the wood pores to play a filling role. The surface of MOFs nanoparticles is smooth and presents a granular cubic structure. The particle size of MOFs is 600-900nm.
[0019] Specifically, in step (5), the rotation speed of the rotating table is 150 rad / min, 20 μL of a Li2S8 solution with a concentration of 0.2 g / mL is added dropwise, and the solvent is a mixed solution of DOL / DME (v:v=1:1).
[0020] The application of the MOFs-modified wood-based self-supporting conductive skeleton is to assemble a button battery with the MOFs-modified wood-based carbon film sulfur-supported self-supporting positive electrode, and the assembly order is negative electrode shell → lithium sheet → 30 μL / mg(s) DOL / DME mixed solution containing 1M LiTFSI and 1.0% LiNO3 → diaphragm → 30 μL / mg(s) DOL / DME mixed solution containing 1M LiTFSI and 1.0% LiNO3 → MOFs-modified wood-based carbon film sulfur-supported self-supporting positive electrode → gasket → spring → positive electrode shell, so as to obtain an LSB with a wood-based sulfur-supported self-supporting positive electrode modified by MOFs.
[0021] Beneficial effects of the present invention:
[0022] The present invention provides a preparation method of a MOFs-modified wood-based carbon film and its energy storage application as a positive electrode of LSB after being loaded with sulfur, which has the following beneficial effects:
[0023] (1) By converting traditional powdered carbon materials into self-supporting carbon matrices, no additional conductive agents, binders, and organic solvents are required when acting on the LSBs self-supporting sulfur cathode. The integrated carbon skeleton can provide convenient ion and electron channels and more sulfur loading and reaction sites. In addition, the self-supporting cathode is easy to control in thickness and can flexibly control the sulfur loading to achieve a dynamic balance between sulfur loading and electrochemical performance, ultimately achieving the goal of improving energy density;
[0024] (2) The wood used in the present invention can be used as an excellent sulfur carrier, which is cheap and easy to obtain. Its natural large-size pores allow it to load sufficient functional components, providing a valuable idea for solving the contradiction between the high sulfur loading density and long cycle life of LSBs. In addition, no toxic or harmful reagents are introduced, which reduces the production cost and is conducive to the industrialization of large-scale carbon-based materials.
[0025] (3) The MOFs used in the present invention not only have a high specific surface area and a porous structure, but also have structurally adjustable characteristics. During the pyrolysis process, they can be converted into an N-doped carbon framework with a large specific surface area and controllable porosity. Combining them with a wood matrix can avoid a large amount of agglomeration during the loading process and the pyrolysis process. Moreover, combining them with a highly conductive carbon skeleton can overcome the low electronic conductivity of MOFs.
[0026] (4) The wood-based conductive skeleton carbon matrix used in the present invention is composed of a large number of oriented, orderly and low-tortuosity micron-sized pores. This pore structure can provide sufficient sulfur storage space and fast ion and electron transmission channels. After loading MOFs, it is beneficial to expose metal catalytic active sites, thereby enhancing the catalytic activity of LiPSs and alleviating the shuttle effect.
[0027] (5) Compared with the aluminum foil-based slurry coated electrode, the self-supporting electrode prepared by the present invention through a simple delignification pretreatment, freeze drying, and high-temperature carbonization process does not require additional binders, conductive agents, and current collectors and can be directly used as an electrode, which not only improves the positive electrode specific capacity but also simplifies the electrode preparation process. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 These are SEM images of the mycelium-based membrane modified by ZIF-8 in Example 2 of the present invention; wherein (a) and (c) represent SEM images of the wood-based membrane modified by ZIF-8 before carbonization, and (b) and (d) represent SEM images of the wood-based membrane modified by ZIF-8 after carbonization.
[0029] Figure 2 This is a 5000-fold EDS image of the ZIF-67 modified wood-based carbon film in Example 1 of the present invention.
[0030] Figure 3 This is a charge and discharge curve diagram of the Ni-MOF modified wood-based self-supporting positive electrode in Example 4 of the present invention.
[0031] Figure 4 This is a graph showing the rate performance of the MOFs-modified wood-based carbon film self-supporting positive electrode in Examples 1-4 of the present invention.
[0032] Figure 5 This is a long cycle performance diagram of the Mil-53 modified mycelium-based carbon film self-supporting positive electrode in Example 3 of the present invention after 50 weeks at 0.1C. DETAILED DESCRIPTION
[0033] The following will be combined with the attached embodiment of the present invention Figure 1-5 As shown, the technical solutions in the embodiments of the present invention are clearly and completely described. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Example 1
[0035] Step (1): Cut the commercially available balsa wood block along the vertical growth direction and punch it with a cutter to obtain a thin round piece with a thickness of 2 mm and a diameter of 16 mm. Boil the wood pieces in deionized water and add a buffer solution containing 1% NaClO2 and 5% CH3COONa to perform chemical delignification treatment. Then take out the wood pieces and repeatedly rinse them with ethanol until they are neutral to obtain delignified balsa wood pieces.
[0036] Step (2): Dissolve 3 mmol of Co(NO3)2·6H2O and 0.03 g of polyvinylpyrrolidone (PVP) in 50 mL of deionized water to obtain a metal salt solution, add the delignified balsamic wood chips obtained in step (1) thereto and stir for 6 hours.
[0037] Step (3): Dissolve 144 mmol of dimethylimidazole (2-MI) and 13 mg of hexadecyltrimethylammonium bromide (CTAB) in 150 mL of deionized water to obtain a ligand solution, slowly add the ligand solution to the metal salt solution of delignified wood chips obtained in step (2), stir vigorously for 2 h, and then age at room temperature for 12 h. After aging, take out the wood chips and wash them with deionized water and ethanol.
[0038] Step (4): Freeze the wood chips obtained in step (3) and transfer them to a freeze dryer for drying for 12 hours (-55°C, 100Pa) to obtain a ZIF-67-loaded wood matrix, neatly arrange them between two graphite plates, place them in a tubular furnace, heat and sinter them in a reducing atmosphere furnace, control the rate to 5°C / min, and sinter at 800°C for 3 hours; obtain a MOFs-modified wood-based carbon matrix.
[0039] Step (5): The MOFs-modified wood-based carbon film obtained in step (4) is sent into a glove box, fixed on a rotating table at a rotation speed of 150 rad / min, 20 μL of a Li2S8 solution with a concentration of 0.2 g / mL is added dropwise, and the solvent is a mixed solution of DOL / DME (v:v=1:1). After standing, a MOFs-modified wood-based carbon film-loaded sulfur self-supporting positive electrode is obtained.
[0040] Step (6): Assemble the button cell with the MOFs-modified wood-based carbon film sulfur-supported self-supporting positive electrode, and the assembly order is negative electrode shell → lithium sheet → 30 μL / mg(s) DOL / DME mixed solution containing 1M LiTFSI and 1.0% LiNO3 → diaphragm → 30 μL / mg(s) DOL / DME mixed solution containing 1M LiTFSI and 1.0% LiNO3 → MOFs-modified wood-based carbon film sulfur-supported self-supporting positive electrode → gasket → spring → positive electrode shell, so as to obtain an LSB with a MOFs-modified wood-based sulfur-supported self-supporting positive electrode.
[0041] The electrochemical performance test of the ZIF-67 modified wood-based carbon film self-supporting positive electrode prepared in Example 1 proved its excellent electrochemical performance as a framework material. The results are as follows Figure 4 As shown, at current densities of 0.1C, 0.2C, 0.5C, and 1C, the first discharge specific capacity was nearly 1142mAh / g, 1012mAh / g, 817mAh / g, and 541mAh / g, respectively. When the current density returned to 0.1C, the positive electrode discharge specific capacity could reach 1133mAh / g, indicating that the ZIF-67 modified wood-based membrane has excellent rate performance. Figure 2 As shown, after high-temperature carbonization, C, N, O, and Co are evenly distributed on the wood carbon skeleton without obvious agglomeration, indicating that metal Co and N elements are successfully introduced and cooperate well with the carbon skeleton.
[0042] Example 2
[0043] Step (1): Cut the commercially available basswood block along the vertical growth direction and punch it with a cutter to obtain a thin round piece with a thickness of 2 mm and a diameter of 16 mm. Boil the wood chips in deionized water and add a buffer solution containing 1% NaClO2 and 5% CH3COONa to perform chemical delignification treatment. Then take out the wood chips and repeatedly rinse them with ethanol until they are neutral to obtain delignified basswood chips.
[0044] Step (2): Dissolve 1 mmol of Zn(NO3)2·6H2O and 0.01 g of polyvinylpyrrolidone (PVP) in 50 mL of deionized water to obtain a metal salt solution, add the delignified forged wood chips obtained in step (1) thereto and stir for 8 hours.
[0045] Step (3): Dissolve 48 mmol of dimethylimidazole (2-MI) and 6 mg of hexadecyltrimethylammonium bromide (CTAB) in 150 mL of deionized water to obtain a ligand solution, slowly add the ligand solution to the metal salt solution of the delignified forged wood chips obtained in step (2), stir vigorously for 2 h, and then age at room temperature for 18 h. After aging, take out the wood chips and wash them with deionized water and ethanol.
[0046] Step (4): Freeze the wood chips obtained in step (3) and transfer them to a freeze dryer for drying for 12 hours (-55°C, 100Pa) to obtain a ZIF-8-loaded wood matrix, which is neatly arranged and sandwiched between two graphite plates, placed in a tubular furnace, and heated and sintered in a reducing atmosphere furnace at a controlled rate of 10°C / min. Sinter at 800°C for 4 hours to obtain a MOFs-modified wood-based carbon matrix.
[0047] Step (5): The MOFs-modified wood-based carbon film obtained in step (4) is sent into a glove box, fixed on a rotating table at a rotation speed of 150 rad / min, 20 μL of a Li2S8 solution with a concentration of 0.2 g / mL is added dropwise, and the solvent is a mixed solution of DOL / DME (v:v=1:1). After standing, a MOFs-modified wood-based carbon film-loaded sulfur self-supporting positive electrode is obtained.
[0048] Step (6): Assemble the button cell with the MOFs-modified wood-based carbon film sulfur-supported self-supporting positive electrode, and the assembly order is negative electrode shell → lithium sheet → 30 μL / mg(s) DOL / DME mixed solution containing 1M LiTFSI and 1.0% LiNO3 → diaphragm → 30 μL / mg(s) DOL / DME mixed solution containing 1M LiTFSI and 1.0% LiNO3 → MOFs-modified wood-based carbon film sulfur-supported self-supporting positive electrode → gasket → spring → positive electrode shell, so as to obtain an LSB with a MOFs-modified wood-based sulfur-supported self-supporting positive electrode.
[0049] The morphology of the ZIF-8 modified wood-based precursor and sintered body prepared in Example 2 is as follows: Figure 1 (a) Figure 1 (b) Figure 1 (c) and Figure 1 As shown in (d), before sintering, ZIF-8 crystals are successfully loaded inside the wood pores to play a filling role, and the surface of ZIF-8 nanoparticles is smooth and presents a granular cubic structure. The particle size of ZIF-8 is approximately 600-900nm. After sintering, ZIF-8 is successfully converted into Zn nanoparticles, and the ZIF-8 skeleton collapses to form Zn / N@CBW with wood.
[0050] Example 3
[0051] Step (1): Cut a commercially available poplar wood block along the vertical growth direction and punch it with a cutter to obtain a thin round piece with a thickness of 2 mm and a diameter of 16 mm. Boil the wood chips in deionized water and then add a buffer solution containing 1% NaClO2 and 5% CH3COONa to perform chemical delignification treatment. Then take out the wood chips and repeatedly rinse them with ethanol until they are neutral to obtain delignified poplar wood chips;
[0052] Step (2): dissolve 3 mmol of FeCl3·6H2O and 0.03 g of polyethylene glycol (PEG) in 50 mL of deionized water to obtain a metal salt solution, add the delignified poplar wood chips obtained in step (1) thereto and stir for 8 h;
[0053] Step (3): dissolving 48 mmol of terephthalic acid and 6 mg of hexadecyltrimethylammonium bromide (CTAB) in 150 mL of deionized water to obtain a ligand solution, slowly adding the ligand solution to the metal salt solution of delignified poplar wood chips obtained in step (2), stirring vigorously for 2 h, and then aging at room temperature for 18 h. After aging, the wood chips are taken out and washed with deionized water and ethanol;
[0054] Step (4): Freeze the wood chips obtained in step (3) and transfer them to a freeze dryer for drying for 12 h (-55°C, 100 Pa) to obtain a MIL-53 (Fe)-loaded wood matrix, neatly arrange the wood matrix between two graphite plates, place the matrix in a tubular furnace, heat and sinter in a reducing atmosphere furnace at a controlled rate of 5°C / min, and sinter at 800°C for 4 h to obtain a MOFs-modified wood-based carbon matrix;
[0055] Step (5): The MIL-53 (Fe) modified wood-based carbon film obtained in step (4) was sent into a glove box, fixed on a rotating table at a rotation speed of 150 rad / min, 20 μL of a 0.2 g / mL Li2S8 solution was added dropwise, and the solvent was a mixed solution of DOL / DME (v:v=1:1), and after standing, a MIL-53 (Fe) modified wood-based carbon film sulfur-loaded self-supporting positive electrode was obtained;
[0056] Step (6): Assemble button cells with the MIL-53(Fe) modified wood-based carbon film sulfur-supported self-supporting positive electrode, and the assembly order is negative electrode shell → lithium sheet → 30 μL / mg(s) DOL / DME mixed solution containing 1M LiTFSI and 1.0% LiNO3 → diaphragm → 30 μL / mg(s) DOL / DME mixed solution containing 1M LiTFSI and 1.0% LiNO3 → MIL-53(Fe) modified wood-based carbon film sulfur-supported self-supporting positive electrode → gasket → spring → positive electrode shell, so as to obtain LSBs using MIL-53(Fe) modified wood-based sulfur-supported self-supporting positive electrode.
[0057] The electrochemical performance of the MIL-53 (Fe) modified wood-based carbon film self-supporting positive electrode prepared in Example 3 was tested. Figure 5 It is shown that after 50 cycles at a current density of 0.1C, the capacity is still maintained at about 814mAh / g, and the single-cycle decay rate is 0.56%. This is attributed to the fact that Fe-MOFs-derived carbon materials can fully expose Fe catalytic sites and nitrogen doping sites, which can more effectively chemically adsorb and catalyze LiPSs conversion, thereby improving its conversion kinetics.
[0058] Example 4
[0059] Step (1): Cut the commercially available pine wood block along the vertical growth direction and punch it with a cutter to obtain a thin round piece with a thickness of 2 mm and a diameter of 16 mm. Boil the wood chips in deionized water and add them into a buffer solution containing 1% NaClO2 and 5% CH3COONa for chemical delignification treatment. Then take out the wood chips and repeatedly rinse them with ethanol until they are neutral to obtain delignified pine wood chips;
[0060] Step (2): 3 mmol Ni(NO3)2·6H2O and 0.03 g polyethylene glycol (PEG) were dissolved in 50 mL deionized water to obtain a metal salt solution, and the delignified pine wood chips obtained in step (1) were added thereto and stirred for 8 h;
[0061] Step (3): dissolving 24 mmol of 2-MI and 3 mg of hexadecyltrimethylammonium bromide (CTAB) in 150 mL of deionized water to obtain a ligand solution, slowly adding the ligand solution to the metal salt solution of delignified pine wood chips obtained in step (2), stirring vigorously for 2 h, and then aging at room temperature for 18 h. After aging, the wood chips were taken out and washed with deionized water and ethanol;
[0062] Step (4): Freeze the wood chips obtained in step (3) and transfer them to a freeze dryer for drying for 12 hours (-55°C, 100Pa) to obtain a Ni-MOF-loaded wood matrix, neatly arrange them between two graphite plates, place them in a tubular furnace, heat and sinter them in a reducing atmosphere furnace at a controlled rate of 5°C / min, and sinter them at a high temperature of 900°C for 2 hours to obtain a MOFs-modified wood-based carbon matrix.
[0063] Step (5): The Ni-MOF modified wood-based carbon film obtained in step (4) was placed in a glove box, fixed on a rotating table at a rotation speed of 150 rad / min, 20 μL of a 0.2 g / mL Li2S8 solution was added dropwise, and the solvent was a mixed solution of DOL / DME (v:v=1:1), and after standing, a Ni-MOF modified wood-based carbon film sulfur-loaded self-supporting positive electrode was obtained;
[0064] Step (6): Assemble the Ni-MOF modified wood-based carbon film sulfur-supported self-supporting positive electrode into a button cell, wherein the assembly order is negative electrode shell → lithium sheet → 30 μL / mg(s) DOL / DME mixed solution containing 1M LiTFSI and 1.0% LiNO3 → diaphragm → 30 μL / mg(s) DOL / DME mixed solution containing 1M LiTFSI and 1.0% LiNO3 → Ni-MOF modified wood-based carbon film sulfur-supported self-supporting positive electrode → gasket → spring → positive electrode shell, thus obtaining an LSB using a Ni-MOF modified wood-based sulfur-supported self-supporting positive electrode.
[0065] The electrochemical performance of the Ni-MOF modified wood-based carbon film self-supporting positive electrode prepared in Example 4 was tested. Figure 3 From the constant current charge-discharge curves of the first week at 0.1C, it can be seen that the Ni-MOF modified wood-based carbon film self-supporting positive electrode has two typical discharge platforms and one charging platform. The voltage platform around 2.3V corresponds to the transformation of S8 to long-chain LiPSs, and the 2.1V platform corresponds to the transformation of long-chain LiPSs to Li2S. The charging platform around 2.4V is the reverse reaction of the above reaction, that is, the oxidation reaction of Li2S to S8.
[0066] The above results can all show that the wood matrix selected by the present invention is a good conductive substrate, which can load excellent catalysts and can be used as a promising LSB self-supporting positive electrode material, which not only simplifies the process, but also increases the sulfur loading of LSB. Biomass wood is used as raw material, cut and de-lignined, and pre-treated. MOFs with Co, Zn, Fe, Ni as metal active centers, dimethylimidazole and terephthalic acid as organic ligands are loaded, and then a freeze-drying method is used to prepare a wood-based self-supporting positive electrode. The freeze-dried mycelium film is sandwiched between two graphite plates, placed in a tubular furnace, and nitrogen is used as a protective gas. The wood-based self-supporting electrode material is obtained by step-heating.
[0067] The present invention utilizes natural wood with a directional ordered pore array with low curvature and good structural stability, and the thickness is easy to control. On the one hand, the appropriate thickness and abundant pores of the wood can greatly increase the sulfur loading, and the appropriate thickness needs to be determined as a standard through sandpaper polishing. On the other hand, its continuous conductive framework and low curvature are conducive to electrolyte penetration to achieve rapid transfer of ions and electrons. However, the ordered pores of wood are large-sized channels at the micron level, lacking functional micro-mesopores, which can easily cause sulfur loss, resulting in serious capacity decay. Therefore, filling and modifying the pores of wood by loading catalysts is an effective way to improve the electrochemical performance of wood-based self-supporting positive electrodes. The wood used in the present invention can be bio-regenerated in large quantities, is cheap and easy to obtain, and the obtained self-supporting positive electrode sheet adopts a stacked assembly battery, and the battery performance test has good electrochemical performance.
Claims
1. A method for preparing a MOFs-modified wood-based self-supporting conductive skeleton, characterized in that: The following steps are involved: Step (1): firstly cut a commercially available wood block along a vertical growth direction and punch it with a cutter to obtain a thin disc with uniform thickness and diameter; boil the thin disc in deionized water and then add it into a buffer solution containing NaClO2 and CH3COONa for chemical delignification treatment; then take out the thin disc and repeatedly rinse it with ethanol until it is neutral to obtain delignified wood chips; Step (2): dissolving metal salts and surfactants of different masses in deionized water to obtain a metal salt solution, adding the delignified wood chips obtained in step (1) to the metal salt solution and stirring with a magnetic stirrer; Obtaining a wood chip metal salt solution; Step (3): dissolving an organic ligand and a capping agent in deionized water to obtain a ligand solution, slowly adding the ligand solution to the wood chip metal salt solution, vigorously stirring with a magnetic stirrer, and then aging at room temperature. After aging, the MOFs-modified wood chips are taken out and washed with deionized water and ethanol; Step (4): the MOFs-modified wood chips are frozen and transferred to a freeze dryer for drying, and then neatly arranged and sandwiched between two graphite plates, placed in a tubular furnace, and subjected to a carbonization process under the protection of a reducing gas atmosphere to obtain a MOFs-modified wood-based carbon film; Step (5): The MOFs-modified wood-based carbon film is placed in a glove box, fixed on a rotating table for rotation, and a DOL / DME mixed solution containing Li2S8 is added dropwise. After standing, a MOFs-modified wood-based carbon film-loaded sulfur self-supporting positive electrode is obtained, i.e., a MOFs-modified wood-based self-supporting conductive skeleton.
2. The method for preparing a MOFs-modified wood-based self-supporting conductive skeleton according to claim 1, characterized in that: The commercially available wood block in step (1) is one of balsa wood, poplar wood, plank wood, basswood, and pine wood; the wood chip has a thickness of 1-3 mm and a diameter of 16-20 mm; The buffer solution was an aqueous solution of 1% NaClO2 and 5% CH3COONa.
3. The method for preparing a MOFs-modified wood-based self-supporting conductive skeleton according to claim 2, characterized in that: The metal salts in step (2) correspond to one or more combinations of Fe, Co, Ni, Zn, and Cu, respectively; the surfactants are one or more combinations of polyvinyl pyrrolidone (PVP) and polyethylene glycol (PEG); the concentration range of the metal salt is 1-6 mmol; the surfactant is 0.01-0.06 g; and the stirring time of the magnetic stirrer is 6-8 h.
4. The method for preparing a MOFs-modified wood-based self-supporting conductive skeleton according to claim 3, characterized in that: The organic ligand described in step (3) is one or a combination of 2-methylimidazole and terephthalic acid, and the concentration range of the organic ligand is 8-144mmol; the magnetic stirring time is 1-3h; the aging time is 6-18h; the capping agent is one or more combinations of hexadecyltrimethylammonium bromide (CTAB) and polyvinyl alcohol (PVA), and the capping agent is 0.01-0.13g.
5. The method for preparing a MOFs-modified wood-based self-supporting conductive skeleton according to claim 1, characterized in that: The drying temperature in step (4) is -55°C, 100Pa, and the time is 12h. The heating rate of the tubular furnace in step (4) is controlled to be 2-10°C / min, and the high-temperature sintering is performed at 700-900°C for 2-4h.
6. The method for preparing a MOFs-modified wood-based self-supporting conductive skeleton according to claim 5, characterized in that: The MOFs-modified wood chips in step (4) are MOFs-loaded wood matrices. MOFs crystals are successfully loaded inside the wood pores to fill the pores. The MOFs nanoparticles have a smooth surface and a granular cubic structure. The particle size of the MOFs is 600-900 nm.
7. The method for preparing a MOFs-modified wood-based self-supporting conductive skeleton according to claim 1, characterized in that: In step (5), the rotation speed of the rotating table is 150 rad / min, and 20 μL of a Li2S8 solution with a concentration of 0.2 g / mL is added dropwise, and the solvent is a mixed solution of DOL / DME (v:v=1:1).
8. The use of the MOFs modified wood-based self-supporting conductive skeleton obtained by the method according to any one of claims 1 to 7, characterized in that: The MOFs-modified wood-based carbon film sulfur-loaded self-supporting positive electrode was assembled into a button cell, and the assembly order was negative electrode shell → lithium sheet → 30 μL / mg(s) DOL / DME mixed solution containing 1M LiTFSI and 1.0% LiNO3 → diaphragm → 30 μL / mg(s) DOL / DME mixed solution containing 1M LiTFSI and 1.0% LiNO3 → MOFs-modified wood-based carbon film sulfur-loaded self-supporting positive electrode → gasket → spring → positive electrode shell, thus obtaining an LSB with a wood-based sulfur-loaded self-supporting positive electrode modified with MOFs.
Citation Information
Patent Citations
Preparation method of lithium / sodium sulfur battery cathode material via metal modified 3D carbon network load metal organic skeleton
CN109728284A
Metal organic framework / wood composite material, and preparation method and application thereof
CN112959446A
MOFs (Metal-Organic Frameworks)-based wood derived membrane as well as preparation method and application thereof
CN117416943A
Monolithic wood-derived cathodes for lithium sulfur batteries
WO2023235627A1